1986
DOI: 10.1002/j.1460-2075.1986.tb04217.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1A-mediated regulation of class I MHC expression.

Abstract: Expression of class I MHC transplantation antigens has been shown to be reduced in baby rat kidney (BRK) cells transformed by highly oncogenic adenovirus type 12 (Ad12), as compared with untransformed cells and cells transformed by non‐oncogenic Ad5. Here we show that this reduction of class I expression also occurs in a variety of other primary cell cultures transformed by Ad12, and that reduction of class I gene expression occurs for all class I loci. Transfection of Ad5E1 into class I‐negative Ad12‐transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 32 publications
2
40
1
Order By: Relevance
“…The stable G401 transfectants 21K-C1 and 21K-C8 (21C1 and 21C8, respectively); 21K/E1A-C3 and 21K/E1A-C24 (5/21C3 and 5/21C24, respectively); 5E1B-C2, 5E1B-C3, and 5E1B-C5 (G55C1, G55C3, and G55C5, respectively); 12E1B-C1, 12E1B-C3, and 12E1B-C7 (G54C1, G54C3, and G54C7, respectively); and E4-C3 and E4-C7 (GE4C3 and GE4C7, respectively) have been described previously (28)(29)(30) and were grown on the same medium with addition of G418 (300 g/ml). Primary HER (human embryonic retina), Ad5-transformed HER XC1 and HER XC2, and Ad12-transformed HER RC4 and HER RC6 cell lines have been described previously (33) and were cultured on Eagle's minimal essential medium supplemented with vitamins, nonessential and essential amino acids, glucose, and 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…The stable G401 transfectants 21K-C1 and 21K-C8 (21C1 and 21C8, respectively); 21K/E1A-C3 and 21K/E1A-C24 (5/21C3 and 5/21C24, respectively); 5E1B-C2, 5E1B-C3, and 5E1B-C5 (G55C1, G55C3, and G55C5, respectively); 12E1B-C1, 12E1B-C3, and 12E1B-C7 (G54C1, G54C3, and G54C7, respectively); and E4-C3 and E4-C7 (GE4C3 and GE4C7, respectively) have been described previously (28)(29)(30) and were grown on the same medium with addition of G418 (300 g/ml). Primary HER (human embryonic retina), Ad5-transformed HER XC1 and HER XC2, and Ad12-transformed HER RC4 and HER RC6 cell lines have been described previously (33) and were cultured on Eagle's minimal essential medium supplemented with vitamins, nonessential and essential amino acids, glucose, and 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Adenovirus 12 (Adl2) transformed cells exhibit reduced levels of MHC class I mRNA and surface class I molecules and are oncogenic when injected into syngeneic animals, whereas cells transformed by Ad5 have unaltered or elevated levels of surface class I molecules and their mRNAs and are non-oncogenic [13][14][15]. Recently it has been shown that TAP1/2 and LMP2/7 mRNA and protein levels are also reduced in Adl2-transformed mouse cells [16,17], and in a number of human tumours [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…They include tumors induced by DNA viruses (15,23,28), RNA viruses (7,17,22), and chemical carcinogens (5). The observed suppression may have arisen either directly by the expression of specific gene products (1)(2)(3)27) or indirectly through mechanisms involving immunoselection (9,20).…”
mentioning
confidence: 99%